2008
DOI: 10.1073/pnas.0709295105
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Mlc–IIB Glc interaction and a plausible molecular mechanism of Mlc inactivation by membrane sequestration

Abstract: In Escherichia coli, glucose-dependent transcriptional induction of genes encoding a variety of sugar-metabolizing enzymes and transport systems is mediated by the phosphorylation state-dependent interaction of membrane-bound enzyme IICB Glc (EIICB Glc ) with the global repressor Mlc. Here we report the crystal structure of a tetrameric Mlc in a complex with four molecules of enzyme IIB Glc (EIIB), the cytoplasmic domain of EIICB Glc . Each monomer of Mlc has one bound EIIB molecule, indicating the 1:1 stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…MecR2 NDD likewise conforms to the structural determinants of such a DBD (see above). The reported structures of Mlc, T. maritima, and V. cholerae are DNA-unbound, and they display the two recognition helices of a dimer in a relative spatial arrangement that is not adequate for binding to two successive turns of the major groove of dsDNA (60,67). This is consistent with the finding that structural flexibility-which allows for major structural rearrangement-of Mlc was identified as essential for DNA binding activity and regulatory function (67).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…MecR2 NDD likewise conforms to the structural determinants of such a DBD (see above). The reported structures of Mlc, T. maritima, and V. cholerae are DNA-unbound, and they display the two recognition helices of a dimer in a relative spatial arrangement that is not adequate for binding to two successive turns of the major groove of dsDNA (60,67). This is consistent with the finding that structural flexibility-which allows for major structural rearrangement-of Mlc was identified as essential for DNA binding activity and regulatory function (67).…”
Section: Resultssupporting
confidence: 77%
“…XylR still binds and is allosterically regulated by sugar. Mlc would represent the next step-as already anticipated in (60)-to a three-domain DNA-binding transcriptional repressor that does not bind sugar and is not regulated by binding to an inducer or by proteolytic cleavage but through sequestration by a glucose transporter, i.e., through a protein-protein interaction (67,76). Finally, MecR2 would represent a last step in the evolutionary process, in which a three-domain ligand-independent Mlc-like repressor would have kept an unspecific DNA binding ability putatively required for biological function as an antirepressor.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, EIIB Glc binds to Mlc in the central part of the protein between the N-terminal DNA binding motif and the C-terminal dimerization domain. This interaction lowers the affinity of the repressor for its target sites (142). However, interaction with the EIIB Glc domain alone does not seem to be sufficient for Mlc inactivation.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…Possibly, cytoplasmic EIIB Glc has a lower affinity for Mlc and might therefore have lost its inhibiting effect. However, fusing the EIIB Glc domain to another membrane protein prevented Mlc activity, suggesting that the interaction with the membrane environment is important for Mlc regulation (141,142). The crystal structure of the complex formed by the EIIB Glc domain and Mlc revealed that Mlc forms tetramers with each subunit binding an EIIB Glc domain.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%